Feminisme dan Kesetaraan Jender dalam Perspektif al-Quran dan Hadis - Muhandis al-Zuhri (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2011)
Feminism point of view - as a modern deliberation of IXth century, coming from western is not a peculiar entity for eastern (read : Islam). The figure of Rasululloh SAW presents that Islam messenger has shown humanist characteristics for females particularly on behalf of wives and Islamic females in earlier era of Islam by respecting jender equality therefore the rights of politics, economy and social between males and females are regarded same, there are no discriminations just by the differences in sex and jender. Perspectives and morality characters shown by Rasululloh SAW to females in this writing is completed by performing explorations through historical and hadists texts concerning females around the Prophet and his best friends. Based on the analysis, it can be concluded that the Holy Prophet Muhammad SAW is a profile of Prophet having feminist, non discriminative, humanist and universal ways of thinking.